2022
DOI: 10.1016/j.hrthm.2021.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Leadless atrioventricular synchronous pacing in an outpatient setting: Early lessons learned on factors affecting atrioventricular synchrony

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
2
40
0
1
Order By: Relevance
“…With this programming, ambulatory AVS percentage increased significantly from 71.9% to 82.6%, similar to AVS at rest with the most pronounced increase during elevated sinus rates between 80 and 110 bpm. Similar findings were reported by Neugebauer et al 11 in an outpatient setting where the authors were able to improve median AVS with a second optimization session occurring between 1-3 months after implantation.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 89%
“…With this programming, ambulatory AVS percentage increased significantly from 71.9% to 82.6%, similar to AVS at rest with the most pronounced increase during elevated sinus rates between 80 and 110 bpm. Similar findings were reported by Neugebauer et al 11 in an outpatient setting where the authors were able to improve median AVS with a second optimization session occurring between 1-3 months after implantation.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 89%
“…Most importantly, their data confirms and is in line with recent reports, 8,9 that the success in achieving AV synchrony in a real-world setting may be lower than the MARVEL 2 clinical trial. The results also emphasize the importance of active programming changes which can significantly improve AV synchrony following an optimization postimplantation.…”
supporting
confidence: 88%
“…Critical programming changes made by performing a manual atrial mechanical (MAM) test while disabling the features that automatically affect these include adjusting the PVAB, A3/A4 windows, and A3/A4 thresholds, and turning off the AV conduction mode (VVI+) in those with complete heart block and escape >40 bpm. The authors and others 8,9 have identified helpful examples of troubleshooting these interval timings and thresholds for optimizing AV synchrony, which an implanter must be familiar with to successfully manage patients with leadless AV synchronous devices. Critically, while performing a MAM test, a key prerequisite for successful interpretation of device tracings is the inclusion of an optimal electrocardiogram tracing.…”
mentioning
confidence: 99%
“…However, LLPMs may—with unknown frequency—still adhere to the tricuspid valve and subvalvular apparatus, posing a challenge if device extraction is performed 25 . Moreover, a functional TR component induced by the non‐physiologic RV stimulation may remain, despite the recently introduced more physiologic LLPMs (i.e., atrio‐ventricular synchronous LLPMs 26 ).…”
Section: Discussionmentioning
confidence: 99%